Impact of Multi-Cloud Infrastructure on Business Organizations to Use Cloud Platforms to Fulfill Their Cloud Needs - Lal, Karu (American Journal of Trade and Policy, 2016)
"Infrastructure as a Service" (IaaS) refers to utilizing various public cloud platforms by Multi-Cloud Infrastructure. This multi-cloud paradigm abstracts the differences between cloud providers so that applications and operational procedures can function in a manner that is uniform across all environments. This makes it possible for businesses to reap the benefits of cloud service providers’ many capabilities while avoiding the risks typically associated with depending on a single cloud service. It is becoming increasingly vital for enterprises to modernize their applications and seamlessly manage and control deployment and scale across environments. As a result, multi-cloud management of the underlying infrastructure is becoming increasingly important. Within the confines of this investigation, we have covered topics such as the relevance of the Multi-Cloud Infrastructure, its many benefits, drawbacks, and other issues. In addition, we have investigated the functions involved in the operation of multi-cloud infrastructure. This piece presents an overview of the multi-cloud infrastructure idea and discusses some recommended procedures.